ANALYSIS OF THE VALUE OF ENGINEERING COST AND TIME OF REPLACEMENT OF RED BRICK WITH LIGHT BRICK ON PROJECT BUILDING CONSTRUCTION OF BLOOD TRANSFUSION UNIT IN PASURUAN (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
The problem in the development of the blood transfusion Unit of Pasuruan building is the cost and time available are limited so the need to do value engineering. Value engineering is used to seek out alternatives or ideas aimed at generating a better or lower cost than the previously planned price with functional restrictions and job quality. So that the results of this value engineering research are expected, that if the work item is following the initial design after the change with an alternative design will be obtained more efficiently in terms of cost plan and time allocation required. The results of the analysis of engineering values for wall items by proposing alternative material instead of initial material, resulting in cost savings of Rp. 7.343.228,77,-from the initial cost. Value engineering can be applied at any time of the project, from the beginning to completion of the project development.